2016
DOI: 10.5792/ksrr.2016.28.3.194
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Blood Loss between Neutral Drainage with Tranexamic Acid and Negative Pressure Drainage without Tranexamic Acid Following Primary Total Knee Arthroplasty

Abstract: PurposeThere are many methods to reduce massive bleeding during total knee arthroplasty (TKA). In our study, tranexamic acid and neutral drainage were used to decrease total blood loss.Materials and MethodsThe study was performed on 97 TKA patients from March 2012 to January 2013. In the study group, tranexamic acid was administered and neutral drainage was applied. The study group had group I (unilateral, n=29) and group III (bilateral, n=17). The control group had group II (unilateral, n=35) and group IV (bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…Both meta-analyses concluded that shed autologous blood reinfusion could significantly reduce the infusion rate and volume of allogeneic red blood cells. However, other studies indicated that shed autologous blood reinfusion was ineffective [68, 15, 16]. This view was discussed in the meta-analysis published in 2015 by Bodegom-Vos et al [9].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both meta-analyses concluded that shed autologous blood reinfusion could significantly reduce the infusion rate and volume of allogeneic red blood cells. However, other studies indicated that shed autologous blood reinfusion was ineffective [68, 15, 16]. This view was discussed in the meta-analysis published in 2015 by Bodegom-Vos et al [9].…”
Section: Discussionmentioning
confidence: 99%
“…Correspondingly, the allogeneic blood transfusion rate reached 22–87% [2, 2022], and the average blood transfusion was 2 units [20]. Some studies [16] suggested that the blood loss in unilateral or bilateral knee arthroplasty can be as high as 1292 and 2043 ml. Similar to this result, the total blood loss caused by unilateral and bilateral knee arthroplasty in this study exceeded 1000 and 2000 ml, respectively, and the transfusion rates were as high as 91–95% and 100%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The daily transition of Hb drop and the estimated blood loss were investigated over an initial 24 h (from the beginning of TKA to 24 h after TKA), from 24 h to 48 h, and from 48 h to 72 h. The blood loss was calculated using the formula developed by Nadler et al; [13][14][15][16] the formula estimates blood volume by accounting for gender, weight, and size of the patient and calculates blood loss using the patient's blood volume and Hb reduction rate. If transfusion was performed, 0.7 g/dL per 1unit (320 mL of packed red blood cells) was added to the value of Hb drop.…”
Section: Methodsmentioning
confidence: 99%
“…Allogenic transfusion can lead to increased length of stay, perioperative infection, and increased cost of treatment. Many methods have been tried to reduce allogenic transfusion, such as oral and intravenous administration of tranexamic acid, or intra-articular or subcutaneous routes to reduce transfusion rate [6][7][8][9]. The auto-transfusion system is a method that reduces allogenic transfusion during TKA [10].…”
Section: Introductionmentioning
confidence: 99%